2008
DOI: 10.1016/s1567-4215(08)60182-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and safety of prolonged levosimendan infusion in patients with acute heart failure

Abstract: Background. Levosimendan is an inotropic drug with unique pharmacological advantages in patients with acute heart failure. Scope of this study is to determine whether longer infusion patterns without the hypotension-inducing loading dose could justify an effective and safe alternative approach. Methods. 70 patients admitted to the emergencies with decompensated chronic heart failure received intravenously levosimendan without a loading dose up to 72 hours. Clinical parameters, BNP (Brain Natriuretic Peptide) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, recent studies showed that levosimendan administration improved contractility in postischemic myocardium in patients with PCI‐treated STEMI complicated by heart failure . However, the use of levosimendan in heart failure is still a matter of debate , and the drug should be probably used in HF to counteract the effect of beta‐blockade .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies showed that levosimendan administration improved contractility in postischemic myocardium in patients with PCI‐treated STEMI complicated by heart failure . However, the use of levosimendan in heart failure is still a matter of debate , and the drug should be probably used in HF to counteract the effect of beta‐blockade .…”
Section: Discussionmentioning
confidence: 99%